Effect of digital payments and sales promotion on beverage franchise product purchase decisions :case study of Haus consumers in Binus branch - muhammad yusuf; Pitri Yandri (STIE Binaniaga, 2021)
Abstract: In the era of globalization, the progress of science and technology is growing very rapidly. In the field of marketing, one of them is by increasingly advanced payment methods and sales promotions. Promotions and digital payments are also strategies to attract consumers to make purchasing decisions. This study aims to determine the partial and simultaneous effect of digital payments and sales promotions on purchasing decisions for thirsty drinks. The population of this research is the consumers of the Haus drinks, Binus branch in West Jakarta, and have made a purchase of Haus. The sampling technique used was non-probability sampling, namely the purposive sampling technique with 80 respondents. The data analysis technique used is the Structural Equation model with SmartPLS. The results of this study indicate that digital payments and sales promotions have a simultaneous effect on purchasing decisions. Partially digital payments and sales promotions have a significant effect on purchasing decisions at the Binus branch of Haus drinks.